Truth and historiographical aims in Polybius' histories - Monti, GAA (2019)
This work looks at the textual exegesis of the passages in which Polybius writes about truth as seen in a historiographical milieu and in relation to what Polybius claims to be the proper way of writing history. The main scholarly contribution and originality of this dissertation are to provide a comprehensive analysis of this concept, since the notion of truth in Polybius’ work has not been yet extensively examined, and at the same time to ‘test’ Polybius’ assessments and check whether he actually stuck to his claims.